1308: Eine Topographie historischer Gleichzeitigkeit - Speer, Andreas; Wirmer, David (De Gruyter, 2010)
The Year 1308 ;Johannes Duns Scotus; Philosophy/ in the Middle Ages; History/ in the Middle Ages; Theology/ in the Middle Ages